Dynamique et morphologie d'un cordon de bloc exposé aux évènements de tempêtes extrêmes, Valahnúkur (Islande) - Massé, Lancelot; Stéphan, Pierre; Didier, D; Suanez, Serge; Autret, Ronan (HAL CCSD, 2022)
International audience